Phase equilibria and thermodynamic evaluation of the Fe-Ti-V-O system in air. (June 2019) - Malan, Willem Dutoit; Akdogan, Guven; Taskinen, Pekka; Zietsman, Johan
Abstract: In this study, the iron-titanium-vanadium-oxygen (Fe-Ti-V-O) system in equilibrium with air was studied experimentally by high-temperature equilibration, quenching, scanning electron microscope and microprobe analysis coupled with critical assessment and thermodynamic evaluation. The properties of the liquid phase were successfully described with the quasichemical model by optimizing parameters only related to the Fe-Ti-O system; remaining parameters for the Fe-V-O and Ti-V-O sub-systems were adopted from recent optimisations. The model for the rutile and hematite solid solutions were described with the compound energy formalism. The ferropseudobrookite solid solution was modelled with a simple polynomial model to include a small solubility V 2 O 5 . A final set of self-consistent thermodynamic parameters was estimated within acceptable error limits. Calculated isothermal projections at 1000 °C, 1100 °C, 1200 °C, 1300 °C, and 1400 °C of the Fe-Ti-V-O system in equilibrium with air are presented and compared to experimental observations.